Evaluation frameworks in health services: An integrative review of use, attributes and elements. Issue 13 (25th March 2019) - Bradford, Natalie; Chambers, Shirley; Hudson, Adrienne; Jauncey‐Cooke, Jacqui; Penny, Robyn; Windsor, Carol; Yates, Patsy
Abstract: Aims and objective: To synthesise the evidence on the use of evaluation frameworks by nurses and midwives in research designed to improve healthcare services and practice. A secondary aim was to identify the attributes and elements of evaluation frameworks. Background: Evaluation is an integral component of any initiative to improve outcomes or change clinical practice. Yet often an evaluation may not yield the information required to sustain or integrate an initiative into practice. Evaluation frameworks can support effective evaluations, but there is a lack of consensus regarding elements and attributes of frameworks that support use. Methods: We undertook an integrative review to synthesise the use of evaluation frameworks in practice guided by the Preferred Reporting Items for Systematic review and Meta‐Analysis flow diagram and checklist 2009 (Supporting Information File 4). The protocol was registered with PROSPERO (CRD42018087033). A broad range of electronic databases were systematically searched using keywords. Findings: Twenty‐five papers were included from a diverse range of clinical areas and across high‐, middle‐ and low‐income nations. Twenty of the research projects had used nine existing frameworks, and five had developed an evaluation specific to an initiative. Frameworks supported the processes of evaluation and made them more meaningful by simplifying a complex process (providing structure and guidance for the evaluation processes); identifying and including stakeholders; explaining reasons for outcomes; generating transferable lessons; and identifying the mechanisms driving or inhibiting change. Conclusion: Nurses and midwives reported that frameworks were useful in undertaking evaluations. Each framework had positive attributes and missing or confusing elements. When undertaking an evaluation, it is pertinent to review the elements and attributes of a framework to ensure it includes evaluation measures that are relevant to specific projects. Relevance to clinical practice: Nurses are actively involved in evaluation of clinical practice. This review identifies important elements to consider when choosing a framework for evaluation.